Επίλυση Προβλημάτων Πεπερασμένων Στοιχείων με Χρήση της Πλατφόρμας FEniCS - Αμαρτωλός, Νικόλαος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών, 2018)
Many computational packages have been developed, that are provided either for free or for a fee, for solving partial differential equations (PDEs) using finite element methods. This master thesis dealt with the use of the FEniCS platform. FEniCS enables users to quickly translate scientific models into efficient and flexi-ble finite element code. It offers two Application Programming Interfaces (APIs), in Python and C ++. In this master thesis, two two-dimensional problems were solved using FEn-iCS libraries. They are a linear and a non-linear problem and the developed codes were written in Python. Internal libraries of FEniCS and the program gmsh were used in order to create the grid. Also, PDEs that describe the problems have been transformed into variational formulation. This formulation is necessary for programming PDEs in FEniCS’ symbolic language. Lastly, the developed codes were converted to parallel using FEniCS and a reduction in run time of up to 63% was achieved.